SPECIAL DENTAL CASE SHEET AS A MEDICAL AND FORENSIC COMMUNICATION TOOL - Kirana, Irin; Sulistiadi, Wahyu; Winata, Tjen Dravinne (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The implementation of the International Classification of Diseases, Tenth Edition (ICD-10 codes) in the medical records serving as the humanitarial tools for practitioners is to establish treatment procedures for re-admitted patients in a hospital. Medical records serves as a tool in determining the appropriate treatment for each patient. But in reality, has never the ICD-10 been applied to the Electronic Medical Record Management. For it to be used as a humanitarian tool, it has first to be used as legal evidence in the court as a written legal system in Indonesia. However, the implementation by the lawyers and relevant officers is under the progress. The result of the previous research showed on the Dental Professionals? Medical Record Form in 2014 at FKG Usakti [29] had determined the need for special dental case sheets as a humanitarian tool between practitioners and dentists. The Special Sheet should meet the specific requirement to be utilized in a class A hospital and it also needs to be standardized with the Indonesian National Police. Methods: In this Systematic Review, the researchers conducted a Proquest database published from January 2012 to June 2019. 10 relevant studies of the medical records were selected as a humanitarian tool in Disaster Victim Identification (DVI) done by the dentist.Results: From 10 present studies and previous studies [29] conducted by the researcher, it had succesfullyidentified the importance of medical record management as a humanitarian tool between practitioners and dentists in hospitals.Conclusion: Special Dental Case Sheet is required for the implementation of collective information which serve as a general humanitarian tool among health professionals. It is required as a comparative data in the identification process if the related patients are the disaster victims.